Food Communication to Strengthen the Javanese Women’s Communication Experience in Indonesia: Case Study on Saparan Bekakak Tradition - Setyaningsih, Rila; Andryani, Kristina; Salsabila, Alya Dwi (Indonesian Journal of Advanced Research, 2025)
Food is an integral part of a region's culture, reflecting the history, traditions, and values of the local community. Food serves as a communication medium. This study examines the communication experience of Javanese women through the communication on Saparan Bekakak, a noble tradition of Indonesia. This study uses the theory of symbolic interactionism to explore communication through food carried out by Javanese women in the Saparan Bekakak tradition. A constructivist paradigm and a qualitative research design are used in this study. The subjects in this study consisted of javaneese woman as the the perpetrator of the Saparan Bekakak tradition. Interviews, observations, and documentation are the collection data technique used in this research. Data analysis in the study consists of several steps (i.e., data reduction, data presentation, and conclusion drawn). This study finds that: 1). The Saparan Bekakak tradition is a significant communication medium for Javanese women to strengthen social and cultural ties. Through the process of preparing and distributing traditional food, women play an active role in preserving cultural values and building a close-knit community, 2) The practice of food communication in the Saparan Bekakak tradition allows Javanese women to express their local identity and wisdom. This is not only a cooking activity, but also a space for the transmission of knowledge between generations and the social empowerment of women in the context of Javanese culture. This research contributes theoretically to the development of the concept of food communication as a complex socio-cultural mechanism, which goes beyond nutritional functions and reveals the strategic role of food in the empowerment of identity and gender relations in the context of local culture.